Mamíferos pequeños en la dieta de la lechuza Tyto alba (Strigiformes: Tytonidae) en dos localidades del occidente de Ecuador, con ampliación distribucional de Ichthyomys hydrobates (Rodentia: Cricetidae) - Brito, Jorge (2015)
We analyzed 107 owl pellets and determined 300 prey items grouped into 21 species. The pellets were collected at two locations with different environments: Los Santiagos and La Ciénaga in the province of Chimborazo and Manabí in western Ecuador. Our analysis revealed a diet mostly comprised on small mammals, especially rodents which constituted 80%. Among the most abundant prey were Oligoryzomys sp. which accounted for 38.7% of the diet in Los Santiagos’ samples and Sigmodon peruanus 33.6% in La Ciénaga, being 22.5% and 41% respectively of the total biomass consumed at each site. The crab-eating rat Ichthyomys hydrobates is first reported in this owl’s diet and in the locality of Los Santiagos. This record extends the distributional range of I. hydrobates to southwest Ecuador by about 200 km. © 2015, Universidade de Sao Paulo. All rights reserved.